2013
DOI: 10.3389/fpsyg.2013.00668
|View full text |Cite
|
Sign up to set email alerts
|

Narrative descriptions should replace grades and numerical ratings for clinical performance in medical education in the United States

Abstract: Background: In medical education, evaluation of clinical performance is based almost universally on rating scales for defined aspects of performance and scores on examinations and checklists. Unfortunately, scores and grades do not capture progress and competence among learners in the complex tasks and roles required to practice medicine. While the literature suggests serious problems with the validity and reliability of ratings of clinical performance based on numerical scores, the critical issue is not that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 53 publications
3
87
0
1
Order By: Relevance
“…have suggested that score variations arise in part because scales may not align with assessors’ thinking, suggesting that ‘disappointing psychometric performance of WBA to date may stem not from disagreements about the performance observed, but from different interpretations of the questions and the scales’. Other authors have suggested that assessments should focus on narrative comments rather than scores . Research into inter‐assessor variability amongst free‐text feedback is far less extensive than has been conducted on assessment scores, although research within occupational psychology indicates that narrative feedback is complex and subject to a variety of influences .…”
Section: Introductionmentioning
confidence: 99%
“…have suggested that score variations arise in part because scales may not align with assessors’ thinking, suggesting that ‘disappointing psychometric performance of WBA to date may stem not from disagreements about the performance observed, but from different interpretations of the questions and the scales’. Other authors have suggested that assessments should focus on narrative comments rather than scores . Research into inter‐assessor variability amongst free‐text feedback is far less extensive than has been conducted on assessment scores, although research within occupational psychology indicates that narrative feedback is complex and subject to a variety of influences .…”
Section: Introductionmentioning
confidence: 99%
“…21 It is remarkable, however, that 60% of our respondents did not believe that pass/fail grading was appropriate for clinical clerkships. One reason for this may be that elimination of grades would then force the system to rely on other variables to make high-stakes decisions, likely leading to an even greater reliance on the results of normative United States Medical Licensing Examination Step Exam scores and Subject Exams.…”
Section: Pass/fail a 3-tier B 4-tier C 5-tier D 6c Tiers E 3-tiermentioning
confidence: 75%
“…For example, different inferences about the target demographic among raters may have contributed to variability [27]. Also, with the lack of clear criteria and limited understanding of each number on the 7‑point scale, raters may have been unable to have a clear and consistent strategy when converting their judgments about a resource into a numerical rating [28]. …”
Section: Discussionmentioning
confidence: 99%
“…There were no clear criteria or anchors defined to convert gestalt opinion into a numerical rating on a scale, which may have contributed to the inconsistency and variability in ratings [28]. While we intentionally kept our anchors vague so that we might best approximate a reader’s innate gestalt, it is possible that a more directed question (e. g. ‘Would you recommend this to a postgraduate year 1 resident?’) would yield a more reliable answer.…”
Section: Discussionmentioning
confidence: 99%